(untitled) (The Pakistan Development Review, 1991)
The Gulf crisis and the suspension of U. S. bilateral assistance to Pakistan for 1990 threaten to have profound economic and political consequences for the . country. These developments are bound to further exacerbate the traditional Balance of Payments difficulties and the unemployment problem in the short run, and possibly the future long-run economic growth of the country. The termination of U. S. assistance for this year is more a reflection of the changing realities of the world today, rather than the alleged temporary measure by the U. S. designed to elicit Pakistan’s cooperation in nuclear non-proliferation. It is highly probable that future U. S. assistance to Pakistan is going to be curtailed and is likely to be on more stringent terms than before.l In such circumstances, an essential question that needs to be answered is that will a reduction in U. S. military and non-military assistance to Pakistan affect significantly its defense capabilities and/or weaken its economy?" Clearly, any objective answer requires an understanding of how the allocation of resources by Pakistan among defense, public non-defense, private investment, and private consumption goods and services is affected by U. S. foreign aid. It is only through this understanding that policy-makers in Pakistan can formulate the requisite strategies to minimize the adverse impacts of the reduction in U. S. assistance. This paper is a step toward furthering that understanding.